Efficacy of a Self-Vaccination Strategy for Influenza A Virus, Mycoplasma hyopneumoniae, Erysipelothrix rhusiopathiae, and Lawsonia intracellularis in Swine - Lucas Caua Spetic da Selva; Rebecca Robbins; Courtney Archer; Madelyn Henderson; Jessica Seate; Luis G. Giménez-Lirola; Ronaldo Magtoto; Arlene Garcia; Allen Jimena Martinez Aguiriano; Emerald Julianna Salinas; John J. McGlone (Vaccines)
Background/Objectives: Environmental enrichment (EE) devices are required in various countries and markets to promote animal welfare, with dual-purpose devices more likely to encourage adoption. We developed an EE device that allows pigs to self-administer liquids, designed to align with natural and play behaviors, and utilized a maternal pheromone (MP) to attract pigs to the device. This study aimed to evaluate the efficacy of this device in delivering vaccines for Erysipelas, Ileitis, Mycoplasma, and Influenza to growing pigs. Methods: Pigs were assigned to three treatments groups: Control (unvaccinated), Hand-Vaccinated (via oral gavage or intramuscular injection), and Self-Vaccinated using the EE device. Baseline samples were collected to determine initial antibody status, and serum and oral fluids’ IgG and IgA levels were measured post-vaccination to assess immune response. Four studies were conducted with 36 pigs (12 per treatment) over a 49-day period. Results: Self-vaccination pigs receiving the avirulent live Erysipelas vaccine developed oral and serum antibodies comparable to Hand-Vaccinated pigs. Pigs self-administering the avirulent live Lawsonia intracelluaris vaccine developed oral fluid antibodies. In contrast, pigs who received Mycoplasma or Influenza vaccines through self-vaccination exhibited significantly lower antibody levels compared to the Hand-Vaccinated group. Conclusions: These findings demonstrated that self-vaccination using EE devices for the oral administration of avirulent live vaccines offers benefits such as reduced labor and improved animal welfare. However, killed vaccines did not elicit sufficient antibody responses, suggesting the need for modified vaccine formulations or administration strategies to improve self-vaccination efficacy.